(3ERgGb GdHGWd aj QO THg GdaQbI GdhgGHjIs - (3eMeO Hf YHO GdhgGH Hf OGhO GdgeOGfj GdcGXej EeGe GdMQejf,J (B1305 (3g` s ((3eMeO GdfLa CHGOi s)
(3ChdgG (B:s
(3CeG HYO ajbhd GdeaJbQ Edi QMeI QHg GdhOhO eMeO Hf YHO GdhgGH hSejJgG HERgGb GdHGWd s
(3BNQgG (B:s
(3hGdYPGH de jcf HSHH GdEYJbGO hGdLgd hGdHZV ddOjf heMHI GdcaQ hEfeG SHHg Cf dg ai Pdc MXkG ef MXhX GdOfjG hGddg JYGdi CYde s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B268s
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B_ (3GdfLa (B(2/1745) s
Keywords: (3GdJhMjO hGdedd hGdfMds